The Moderating Role of Market Competition on the Relationship Between Auditor Experience and Audit Expectation Gap with Audit Quality and Audit Fees in Companies Listed on the Iraq Stock Exchange - Majid Sahaeb Al-Haideri, Rasool; Dastgir , Mohsen; Abdulhasan Jasim, Faez; Saedi , Rahman (Business, Marketing, and Finance Open, 2025)
This study examines the impact of the audit expectation gap on audit quality and audit fees in Iraq's competitive market. The primary objective of the research is to analyze the relationship between the expectation gap, auditor experience, and market competition with audit quality and audit fees. To conduct this study, statistical models and data related to auditors and audit firms in Iraq were utilized. The results indicate that auditor experience has a positive and significant effect on audit quality, and market competition can enhance the impact of auditor experience on audit quality. Additionally, the audit expectation gap has a negative and significant relationship with audit quality. Moreover, market competition exacerbates the impact of the audit expectation gap on audit fees. Based on its findings, this research recommends that audit firms focus on enhancing auditor experience and managing market competition. Furthermore, it is suggested that future research incorporate more diverse criteria for assessing the expectation gap and market competition to achieve more comprehensive results.